Peran Keluarga dan Masyarakat dalam Menanamkan Nilai Toleransi melalui Pendidikan Multikultural - Siti Sarah Sari Mangunsong; Nurhalizah Maharaja; Azizah Hanum OK (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This research examines how families and communities play a role in instilling the value of tolerance through multicultural education. As a country rich in ethnic, religious, cultural and linguistic diversity, Indonesia needs an attitude of mutual respect so that social life continues to run in peace and harmony. Therefore, it is important to introduce the value of tolerance from an early age through the child's closest environment, such as family, community and school. In everyday life, the family is the first place where children receive education about tolerance through providing understanding, habituating positive behavior, example from parents, and monitoring children's attitudes. On the other hand, society also has a contribution as a learning environment that introduces children to diversity through social interaction and various joint activities. Schools also play a role in forming a tolerant character by implementing multicultural education in a planned and sustainable manner. This research uses a literature study method by examining various scientific sources related to multicultural education and instilling the value of tolerance. Based on the results of the study, it is known that cooperation between family, school and community has a very important role in shaping children's character so that they are able to appreciate differences, live side by side in harmony, and maintain unity in the life of a diverse society.